Physicochemical Characteristics and Antioxidant Activities of God’s Crown Fruit (Phaleria macrocarpa) with Variation of Roasting Processes - Arita Dewi Nugrahini; Ferninda Berliana Prasanti; Putri Noviani (Agroindustrial Journal, 2022)
Roasting process is the most important process in processing Phaleria macrocarpa (also called as Mahkota Dewa/God’s Crown) into dried tea product. It aims to change the color, texture, and reduce the water content of Phaleria macrocarpa to extend the shelf life and simplify the distribution and serving process. This study aims to determine the effects of temperature and time in the roasting process on the physicochemical properties of Phaleria macrocarpa including water content, color, texture, and their effect on antioxidant activity (AOA) using DPPH method. The design experiment for this study was by varying the treatments at temperature of 80℃, 100℃, and 120℃ and time at 40, 60, and 80 minutes in the process of roasting Phaleria macrocarpa fruit. Furthermore, the tea of Phaleria macrocarpa produced in each treatment and the standard samples from the industry were analyzed for its physicochemical properties and antioxidant activities. The results of multiple regression analysis showed that the correlation coefficient (r value) between the variables of temperature and time on water content, color, and AOA was 0.827; 0.944; and 0.886 respectively. Increasing temperature and roasting time caused a decrease in water content, color and AOA; however, multiple regression analysis showed a weak correlation between temperature and time on the texture of Phaleria macrocarpa with a correlation coefficient (r value) of 0.095. The best treatment based on research that has been done was found at a temperature of 100℃ for 60 minutes with a total score of effectiveness index (EI) of 0.688. In this treatment it was found the average water content at 1.31 ± 0.20%, lightness at 21.80, redness at 5.10, yellowness at 9.65, texture at 1.16 kgf, and AOA at 82.33 ± 0.30%. Meanwhile, the best physicochemical characteristics and AOA based on the effectiveness index showed results close to the standard sample test values. The slight difference was found in the value of the water content in which at the same temperature and roasting time it showed different values between the test samples and standard samples. The water content in standard samples showed a higher value, probably due to poor storage process. Hence, it is deemed necessary to improve the storage process of Phaleria macrocarpa tea product on industrial scale.